Immunomodulating Effects Depend on Prolactin Levels in Patients with Hyperprolactinemia - Ewerman, Lea; Landberg, Eva; Hellberg, Sandra; Hovland, Mina; Sundin, Anna; Jenmalm, Maria C.; Ekman, Bertil; Ernerudh, Jan; Wahlberg, Jeanette (Hormone and Metabolic Research, 2020)
Prolactin is known to have immune modulatory effects acting through the prolactin receptor, which is present on a variety of immune cells. Certain chemokines contribute to form the type of T helper (Th) preponderance in the immune response. The objective of this work was to assess if hyperprolactinemia not related to pregnancy is associated with changes in circulating levels of chemokines and other immunological markers. In this cross sectional study, 35 patients with hyperprolactinemia (5 men), and 102 healthy blood donors (19 men) were included. Serum levels of Th1- Th2- and Th17-associated chemokines, C-reactive protein, immunoglobulins, and the B cell attracting chemokine CXCL13 were assessed. The hyperprolactinemic group had significantly higher levels of Th2 associated CCL22 (p=0.022), Th17 associated CXCL1 (p=0.001), B cell attracting CXCL13 (p=0.003), and C-reactive protein (p<0.001) compared to controls, and these proteins were also positively correlated with prolactin levels. While differences in CCL22, CXCL1, CXCL13, and C-reactive protein were present in patients with low or moderate hyperprolactinemia, no differences were observed at high (>3600 mU/l) prolactin levels. To evaluate a possible dose-associated response to prolactin, an in vitro model was used, showing prolactin-induced increase in T-helper cell activation at moderate levels, while activation decreased at higher levels. Hyperprolactinemia seems to have several immunomodulatory effects and was associated with increased levels of chemokines associated with Th2 and Th17 responses and B cell attraction. However, patients with greatly increased prolactin had normal levels of chemokines, and in vitro, high levels of prolactin decreased T-helper cell activation.
Keywords: chemokines; autoimmunity; prolactin; hyperprolactinemia